2022
DOI: 10.18203/2349-3291.ijcp20221855
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of neurological disorders in children: a hospital-based experience of a tertiary care centre in Kashmir

Abstract: Background: Neurological disorders in paediatric age group constitute a major cause of hospital visits both elective and emergent. Due to fast maturity of nervous system within the first few years of life they are more prone to neurological disorders, which mostly can be preventive and rehabilitative in nature. Purpose of this study was to know the pattern and spectrum of neurological disorders among children presenting to a tertiary health care facility in Kashmir.Methods: This was a retrospective analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…The high percentage of seizure disorders may be due to increased awareness that these are medical conditions that can be treated. Cerebral palsy in 26 (19.5%) patients was the second most common neurological disorder in our study which is similar to other studies [ 8 , 11 , 14 - 15 ]. Many of the affected children require specialized care and rehabilitative services and multidisciplinary teamwork.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The high percentage of seizure disorders may be due to increased awareness that these are medical conditions that can be treated. Cerebral palsy in 26 (19.5%) patients was the second most common neurological disorder in our study which is similar to other studies [ 8 , 11 , 14 - 15 ]. Many of the affected children require specialized care and rehabilitative services and multidisciplinary teamwork.…”
Section: Discussionsupporting
confidence: 92%
“…Child neurology and developmental pediatrics are not well established at the primary level in developing countries; primary care centers lack basic diagnostic and treatment facilities for the management of childhood neurological disorders. Male predominance was found to be consistent with earlier studies from India that reported higher prevalence among males as compared to females [ 8 - 10 ]; a similar pattern of male predominance was also found in other parts of the world [ 11 - 12 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation